Antipyretic effect of Cymbopogon citratus ethanol extract on yeast-induced fever in mice - Septyasari, Avanilla Fany; Putri, Aristhasari; Sholihatun, Anik (Borobudur Pharmacy Review, 2025)
Lemongrass (Cymbopogon citratus) contains several secondary metabolites, one of which is flavonoids that have the ability to inhibit the activity of cyclooxygenase enzymes. Aims of this study is to determine the efficacy of lemongrass stem ethanol extract (Cymbopogon citratus) as an antipyretic and to determine the minimum effective dose for reducing fever in mice (Mus musculus) induced by yeast. The type of study is an experimental laboratory study, divided into 5 treatment groups, 0.5% CMC Na, paracetamol, lemongrass stem extract at doses of 4 mg/20 g, 6 mg/20 g, and 8 mg/20 g. Fever in mice was induced by subcutaneous injection of a 1.5% yeast solution. Rectal temperature measurements were taken at regular intervals at 30, 60, 90, 120, 150, and 180 minutes. The test results showed that the ethanol extract of lemongrass stem at a dose of 4 mg/20 g was able to reduce the fever-induced temperature of mice by 0.78Â°C from the fever temperature, while the 8 mg/20 g dose of lemongrass extract exhibited antipyretic effects similar to paracetamol.